Lessons from IFPRI Country Programs on Informing Policy Decisions and Strengthening Capacity - Hazell, Peter; Place, Frank (2019)
Peter Hazell and Frank Place POLICY SEMINAR Lessons from IFPRI Country Programs on Informing Policy Decisions and Strengthening Capacity Co-Organized by IFPRI and the CGIAR Research Program on Policies, Institutions, and Markets (PIM) MAY 22, 2019 - 12:15 PM TO 01:45 PM EDT